2010
DOI: 10.1158/1055-9965.epi-19-3-aspo10
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Underserved Women with Mammography: 15 month experience with a Mobile Prevention Unit and Prevention Program

Abstract: Purpose: Despite incidence rates that have been rising for decades, the molecular underpinnings that support the development of clear cell renal cell carcinoma (ccRCC) remain unclear. Herein, we evaluate expression levels of the hypoxia-induced autocrine survival factor endothelin-2 (EDN2) in patient-matched ccRCC and normal kidney samples.Methods: We identified 169 patients who underwent nephrectomy for histologically confirmed, localized ccRCC at our institution from 2000 to 2003 and had fresh-frozen tumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Mobile clinics are used for mammography screenings, 1 diabetes screenings, 2 dental clinics, 3 sexually transmitted infection screenings, 4,5 HIV antibody screenings, 5,6 cancer screenings, 7 and general care clinics. 8 However, a review of the literature found no mobile health clinics in use on college campuses serving the health needs of college students.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Mobile clinics are used for mammography screenings, 1 diabetes screenings, 2 dental clinics, 3 sexually transmitted infection screenings, 4,5 HIV antibody screenings, 5,6 cancer screenings, 7 and general care clinics. 8 However, a review of the literature found no mobile health clinics in use on college campuses serving the health needs of college students.…”
mentioning
confidence: 99%